The Legal Implications and Regulatory Dualism of Cryptocurrency as a Payment Instrument in Indonesia - Nadjima, Aulia Rachmatullah; Satino (Fakultas Syariah INSURI Ponorogo, 2025)
The rapid development of blockchain technology has positioned cryptocurrency as a significant innovation within the global financial system. In Indonesia, its legal status remains controversial due to regulatory dualism between monetary and commodity authorities. This study examines the legal status of cryptocurrency as a payment instrument under Indonesian positive law, employing a normative juridical method that incorporates statutory and conceptual approaches. The findings show that cryptocurrency is explicitly prohibited as a means of payment under Law Number 7 of 2011 on Currency, particularly Article 21 paragraph (1), which mandates the Rupiah as the sole legal tender. Violations are subject to criminal sanctions under Article 33, including imprisonment of up to one year or fines of up to IDR 200 million. This prohibition is reinforced by Bank Indonesia Regulation No. 19/12/PBI/2017, which prohibits the use of virtual currencies in payment systems. Conversely, cryptocurrency is legally recognized as a tradable digital asset under Bappebti Regulation No. 8 of 2021 and supervised under OJK Regulation No. 27 of 2024 within the commodity and investment framework. This regulatory dualism creates legal uncertainty, exposing users to both criminal liability and consumer protection risks. The study concludes that regulatory harmonization among Bank Indonesia, OJK, and Bappebti is necessary to ensure legal certainty and financial system stability.